Macroprudential policy under uncertainty - Venter, Zoë (2022)
In this paper, an index of domestic macroprudential policy tools is constructed and the efectiveness of these tools in controlling credit growth, managing GDP growth and steadying infation is studied using a dynamic panel data model for the period between 2000 and 2017. The empirical analysis includes two panels namely an EU panel of 27 countries and a Latin American panel of 7 countries, the paper also looks at a case study of Japan, Portugal and the UK. Our main results show that a tighter overall macroprudential policy stance would result in lower credit growth as well as lower GDP growth while, a tighter overall macroprudential policy tool stance would lead to higher infation in the majority of cases. Factors such as capital openness and the perception of global market risk play an important role in both the exigency of policy implementation as well as the success thereof.